The church and politics : a theological reflection - Boyo, Bernard (Bukuro, Plateau State, Nigeria, HippoBooks, an imprint of ACTS and Langham Publishing, 2021)
"The Church in Politics offers an introduction to African political theology that is thorough, practical, and deeply powerful. From traditional power structures to the political ramifications of colonialism, Dr. Bernard Boyo provides a foundation for understanding Africa's contemporary political concerns in their cultural and historical context. Alongside this overview of African political history, Boyo traces the impact of Western missionaries, evangelicals, liberation theology, and African theologians on the church's understanding of itself and its role within society. This book critiques the emphasis on individual salvation that has so often led the church into abdicating its societal responsibilities and provides an exegetical analysis that firmly roots political engagement within a scriptural framework. The church, we are reminded, has a mandate to bring justice and righteousness into every aspect of human experience. As we follow Christ, it is not just our personal lives that should be transformed but our communities and even our nations"--page 4 of cover.
Foreword -- Preface -- Introduction -- Part One: The problem in African political engagement. Requirements of an African political theology -- Trends in African political history -- Characteristics of traditional African politics -- Contemporary issues in African politics -- Part Two: Theological approaches to politics. Political theological thought -- Bible and politics -- Politics and praxis -- Conclusion -- Bibliography.
Includes bibliographical references (pages 193-206) and index.
Keywords: Christianity and politics -- Africa; Political theology -- Africa